3
$\begingroup$

There are four numbers. The first three make an arithmetic progression, and the last three make a geometric progression. The sum of first and last number is $37$. The sum of middle numbers is $36$. Find the numbers.

So I'm trying to solve this problem for about 2 hours now. I can't use any formulas because all I get $0=0$. I don't know all the terms in English so I'll just try to upload my notes here. Eh but it doesn't let me. At first i got that $a_1=-2d$, $d$ was $= -36$ so my numbers were $72$, $36$, $0$, $-35$. The problem is that last 3 numbers doesn't make a geometric progression.

$\endgroup$
2
$\begingroup$

Let's say the numbers are $a+d$, $a$, $a-d$, and $\dfrac{(a-d)^2}{a}$. The sum of the middle numbers is $$36=a+(a-d)=2a-d\,.$$ The sum of the other two numbers is $$37=(a+d)+\frac{(a-d)^2}{a}=(2a-d)+\frac{d^2}{a}=36+\frac{d^2}{a}\,.$$ That is, $a=d^2$. Hence, your numbers are $$d^2+d\,,\,\,d^2,d^2-d\,,\text{ and }d^2-2d+1\,.$$ It should be easy now.

You have $(2d-9)(d+4)=2d^2-d-36=(2a-d)-36=0$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thank you so much! $\endgroup$ – Viktoras Bražas Sep 17 '18 at 18:43
1
$\begingroup$

Denoting the numbers $a,b,c,d$, we have the following system of equations:

$$\begin{cases}a+c=2b, \\bd=c^2, \\a+d=37, \\b+c=36.\end{cases}$$

We eliminate $a,b,d$ with $$b=36-c,\\a=2b-c=72-3c,\\d=37-a=3c-35$$

and finally,

$$(36-c)(3c-35)=c^2.$$

The solutions of this quadratic equation are

$$c=20\lor c=\frac{63}4$$ and the other numbers follow.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Some hints:

Call the second and third numbers $x$ and $y$. Find the first and the fourth numbers in terms of $x$ and $y$. Then write up the equations implied by the text, and solve them.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

The first 3 are in arithmetic progression

$a-n, a, a+n, \cdots$

the last 3 are in geometric progression.

$\cdots, a, ra, r^2 a$

There are 4 numbers total.

That means that the 3d element must fit both the geometric and the arithmetic progression

$ra = a+n$

The middle two sum to 36

$a+ra=a(r+1) = 36\\ r = \frac{36}{a} - 1\\ 36 -2a = n$

The first and last sum to 37

$a-n + r^2 a = 37$

And now we use the substitutions above to get everything in terms of a.

$a-n + r(ra) = 37\\ a-n + r(a+n) = 37\\ a-(36-2a) + r(a+36-2a) = 37\\ 3a-36 + r(36-a) = 37\\ 3a-36 + (\frac {36}{a} - 1)(36-a) = 37\\ 3a - 36 + \frac {36^2}{a} - 36 - 36 + a = 37\\ 4a + \frac{1296}{a} - 145 = 0$

Which multiplies into a quadratic.

$4a^2 -145a + 1269 = 0\\ (a-16)(4a-81) = 0$

$a = 16, a = \frac {81}{4}$

If our sequence is integers....

$12, 16, 20, 25$

If our sequence could include rationals... $\frac {99}{4}, \frac {81}{4}, \frac {63}{4}, \frac {49}{4}$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.